2023
DOI: 10.3390/ijms24076297
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanides as Calcium Mimetic Species in Calcium-Signaling/Buffering Proteins: The Effect of Lanthanide Type on the Ca2+/Ln3+ Competition

Abstract: Lanthanides, the 14 4f-block elements plus Lanthanum, have been extensively used to study the structure and biochemical properties of metalloproteins. The characteristics of lanthanides within the lanthanide series are similar, but not identical. The present research offers a systematic investigation of the ability of the entire Ln3+ series to substitute for Ca2+ in biological systems. A well-calibrated DFT/PCM protocol is employed in studying the factors that control the metal selectivity in biological system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The competition between La 3+ /Ln 3+ and Ca 2+ in calcium-binding proteins has been studied before using both experimental and computational techniques as the lanthanum/lanthanide substitution of the native calcium cation appears beneficial in determining the structural characteristics of the host Ca 2+ proteins. 21,28–41 Notably, the present study deepens our understanding about the basic principles governing the Ca 2+ /La 3+ competition from the perspective of lanthanum-binding proteins.…”
Section: Introductionmentioning
confidence: 64%
“…The competition between La 3+ /Ln 3+ and Ca 2+ in calcium-binding proteins has been studied before using both experimental and computational techniques as the lanthanum/lanthanide substitution of the native calcium cation appears beneficial in determining the structural characteristics of the host Ca 2+ proteins. 21,28–41 Notably, the present study deepens our understanding about the basic principles governing the Ca 2+ /La 3+ competition from the perspective of lanthanum-binding proteins.…”
Section: Introductionmentioning
confidence: 64%
“…Recently, it was reported that Gd 3+ is a lanthanide ion that could be considered a calcium mimetic in calcium-signaling/buffering proteins [ 44 ]. Considering that Gd 3+ inhibits Ca-dependent enzymes and voltage-activated channels, several physiological consequences could occur.…”
Section: Discussionmentioning
confidence: 99%
“…Y 2 O 3 NPs, for instance, localize to acidifying intracellular lysosomes after they are taken up by BMSCs, and they undergo dissolution and transformation from Y 2 O 3 NPs to Y 3+ [ 29 ]. Most RE ions have biological properties similar to those of Ca 2+ and exhibit the ability to structurally or functionally replace Ca 2+ to exert positive or negative effects on bone regeneration [ 30 ].…”
Section: Physicochemical Properties and Biological Advantages Of Re Nmsmentioning
confidence: 99%